Teaching Video NeuroImage: Reverse Ocular Bobbing as a Presenting Feature of Brainstem Cavernoma. (4th April 2023) - Singh, Kavindra; Salunke, Pravin
Abstract : A 21-year-old man presented with oscilopsia, repetitive eye blinking, and headache for 20 days. He had intact vision with normal pupillary reaction. Although the horizontal and vertical gazes were intact, there were abnormal conjugate vertical movements with quick up phase followed by slow return to midposition suggestive of reverse ocular bobbing (Video 1). Bobbing was present in all directions of gaze and was associated with synkinetic lid movements. Imaging suggested a dorsal pontine cavernoma (Figure). The patient opted for radiosurgery. Omnipause neurons in dorsal pons tonically inhibit the rostral interstitial nucleus of the medial longitudinal fasciculus burst neurons (center for vertical saccades) which also indirectly stimulates levator subnucleus. 1 Damage to omnipause neurons or connections may cause reverse ocular bobbing with synkinetic lid movements. Unlike ocular bobbing, the horizontal gaze is intact because of uninvolved paramedian pontine reticular formation. 2 Interestingly, reverse ocular bobbing has been previously reported in cases of metabolic encephalopathy but is rarely associated with a structural lesion.